Combining Bottom‐Up Self‐Assembly with Top‐Down Microfabrication to Create Hierarchical Inverse Opals with High Structural Order. Issue 34 (3rd June 2015) - Schaffner, Manuel; England, Grant; Kolle, Mathias; Aizenberg, Joanna; Vogel, Nicolas
<x xml:space="preserve">Abstract</x> Colloidal particles can assemble into ordered crystals, creating periodically structured materials at the nanoscale without relying on expensive equipment. The combination of small size and high order leads to strong interaction with visible light, which induces macroscopic, iridescent structural coloration. To increase the complexity and functionality, it is important to control the organization of such materials in hierarchical structures with high degrees of order spanning multiple length scales. Here, a bottom‐up assembly of polystyrene particles in the presence of a silica sol–gel precursor material (tetraethylorthosilicate, TEOS), which creates crack‐free inverse opal films with high positional order and uniform crystal alignment along the (110) crystal plane, is combined with top‐down microfabrication techniques. Micrometer scale hierarchical superstructures having a highly regular internal nanostructure with precisely controlled crystal orientation and wall profiles are produced. The ability to combine structural order at the nano‐ and microscale enables the fabrication of materials with complex optical properties resulting from light–matter interactions at different length scales. As an example, a hierarchical diffraction grating, which combines Bragg reflection arising from the nanoscale periodicity of the inverse opal crystal with grating diffraction resulting from a micrometer scale periodicity, is demonstrated.